2012
DOI: 10.1002/adfm.201200224
|View full text |Cite
|
Sign up to set email alerts
|

Selective Enhancement of Photoluminescence in Filled Single‐Walled Carbon Nanotubes

Abstract: The insertion of organometallic molecules into the hollow core of singlewalled carbon nanotubes can drastically change their properties. Using biocompatible standardized suspensions of pristine, opened, and fi lled nanotubes, a very selective enhancement of the photoluminescence and optical absorption is observed. Via ferrocene encapsulation, the PL signal increases almost by a factor of three for tubes with chiralities such as (8,6) and (9,5). This behavior is attributed to a local electron charge transfer fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 46 publications
(77 reference statements)
6
75
0
1
Order By: Relevance
“…[ 20 ] On the other hand, the charge transfer already starts causing this deviation in the Raman frequency from the vacuum case for chains containing around 20 carbon atoms. Therefore, the stronger enhancement in absorption features caused by shorter chains rather than the longest ones bears a striking resemblance to the enhancement of absorption features (and photoluminescence intensity) found for SWCNT fi lled with ferrocene: [ 18 ] There, the best enhancement was attributed to an optimum value for the n-type doping of the SWCNT by the ferrocene molecule, cancelling out the p-type doping from the opening process and the surfactant molecules. In our case, an optimum value for the charge transfer from the inner tube to the carbon chain given by the chain length has a similar effect, nullifying the outer tubes charge transfer to the inner tube.…”
Section: Optical Absorption Of the Differently Treated Dwcnt Samplesmentioning
confidence: 74%
See 1 more Smart Citation
“…[ 20 ] On the other hand, the charge transfer already starts causing this deviation in the Raman frequency from the vacuum case for chains containing around 20 carbon atoms. Therefore, the stronger enhancement in absorption features caused by shorter chains rather than the longest ones bears a striking resemblance to the enhancement of absorption features (and photoluminescence intensity) found for SWCNT fi lled with ferrocene: [ 18 ] There, the best enhancement was attributed to an optimum value for the n-type doping of the SWCNT by the ferrocene molecule, cancelling out the p-type doping from the opening process and the surfactant molecules. In our case, an optimum value for the charge transfer from the inner tube to the carbon chain given by the chain length has a similar effect, nullifying the outer tubes charge transfer to the inner tube.…”
Section: Optical Absorption Of the Differently Treated Dwcnt Samplesmentioning
confidence: 74%
“…Normalization of the different suspensions with respect to their optical density was achieved by taking the minimum between the fi rst and second optical transition of the inner tubes. [ 14,18 ] …”
Section: Characterization By Optical Absorption and Photoluminescencementioning
confidence: 99%
“…According to the data presented in reports on the experimental and theoretical investigations of the electronic properties of filled SWCNTs, the following substances have an electron donor effect on the nanotubes: molecules -organic molecules (tetrakis(dimethylamino)ethylene (TDAE) and tetrathiafulvalene (TTF) [48,356]) and organometallic molecules (Co(C 5 H 5 ) 2 , Co(C 5 H 4 C 2 H 5 ) 2 [47,399,400], Fe(C 5 H 5 ) 2 [50,260,262,263,265,267,399,400], Ce(C 5 H 5 ) 3 [51,269], M(C 5 H 5 ) 2 , M= V, Cr, Mn, Ni [399]) and simple substances -metals (Ag [46,293,294,296,315,365,401], Cu [293,295], Eu [272,402], Li, K [403], Ti, Zn, Co, Ni, Fe, Mo, Gd, Cu [402,[404][405][406][407][408][409][410]). …”
Section: Typical Donors Of Electrons and Methods Of Their Encapsulationmentioning
confidence: 99%
“…The filling of the nanotubes with organic molecules (TDAE, TTF [48,356]) and organometallic molecules (Co(C 5 H 5 ) 2 , Co(C 5 H 4 C 2 H 5 ) 2 112 [47], Fe(C 5 H 5 ) 2 [50,260,262,263,265,267], Ce(C 5 H 5 ) 3 [51,269]) was performed via the gas phase method (see section 5.2.2), which resulted in clean samples suitable for further spectroscopic investigations. It should be noted that it was also reported that the incorporation of ferrocene Fe(C 5 H 5 ) 2 into the nanotubes can be performed by the liquid phase method using its solution in an organic solvent [284].…”
Section: Typical Donors Of Electrons and Methods Of Their Encapsulationmentioning
confidence: 99%
“…of nanotubes filled with foreign materials. Recent in-depth study has revealed more applications for these 1D nanomaterials of nanowires sheathed inside nanotubes [76,[135][136][137][138]. However, a systematic review on manipulation, property analysis and potential applications of these inorganic nanowires filled nanotubes using the in-situ HRTEM techniques has not yet been presented.…”
Section: Introductionmentioning
confidence: 99%